PENGARUH FINANCIAL KNOWLEDGE, FINANCIAL ATTITUDE, LOCUS OF CONTROL dan FINANCIAL SELF-EFFICACY TERHADAP FINANCIAL MANAGEMENT BEHAVIOR MASYARAKAT SALATIGA - Tri, Tri Widodo; Elisa Irawati; Yanuar Tri Jayuna Wibisono (Fakultas Ekonomi, Bisnis dan Humaniora, 2025)
A prosperous life is the desire of every individual. Financial management is a reflection of well-being. Every individual is required to be skilled and have sufficient ability and understanding. Financial problems will arise as a result of financial management failure. The purpose of this study is to examine whether Financial Knowledge, Financial Attitude, Locus of Control, and Financial Self-Efficacy influence Financial Management Behavior. The object of the study was the Salatiga community. Due to limitations, the sample in this study was 130 respondents. Sampling used probability sampling. The data analysis tool to answer the hypothesis was multiple regression analysis. The research results partially explain that financial knowledge, financial attitude, and locus of control have a significant effect. Meanwhile, financial self-efficacy does not have a significant effect on financial management behavior. The research results prove that financial knowledge, financial attitudes and behavior, self-control, and self-confidence towards finances are capital in financial planning, as a basis for someone to manage finances better, so that their financial behavior becomes more focused, which ultimately someone is able to achieve a prosperous life.